2008
DOI: 10.1186/1472-6882-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumer and pharmacist views on the professional role of the pharmacist with respect to natural health products: a study of focus groups

Abstract: BackgroundNatural health products (NHPs) such as herbs, vitamins and homeopathic medicines, are currently available for sale in most Canadian pharmacies. However, most pharmacists report that they have limited knowledge about these products which have been regulated in Canada as a specific sub-category of drugs. In this paper, consumers' and practicing pharmacists' perceptions of pharmacists' professional responsibilities with respect to NHPs are examined.MethodsA total of 16 focus groups were conducted with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 18 publications
9
93
1
1
Order By: Relevance
“…Kwan reported that focus groups of consumers and practicing pharmacists thought that pharmacists should adopt a consultative role to help consumers integrate different sources of NHP-related information . 9 This is represented most prominently in Professional NHP-related Competency No. 3: Educate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kwan reported that focus groups of consumers and practicing pharmacists thought that pharmacists should adopt a consultative role to help consumers integrate different sources of NHP-related information . 9 This is represented most prominently in Professional NHP-related Competency No. 3: Educate.…”
Section: Resultsmentioning
confidence: 99%
“…The goal was to develop NHP-related core competencies, consistent with existing competency-based outcomes and standards of practice documents, 27,30,31 informed by previous qualitative research including: a document analysis, 32 35 key informant interviews, 10 16 focus groups with practicing pharmacists and consumers, 9 results from herbal knowledge testing of fourth-year Canadian pharmacy students, 11 and results from a survey of 3356 practicing Canadian pharmacists. 33 This project was approved by the University of Toronto Office of Research Ethics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys conducted in Canada and Australia reported that pharmacy customers would prefer to consult pharmacists for advice on dietary supplements. 17 Therefore, pharmacists must be equipped with evidence-based knowledge to provide an unbiased opinion and counseling about the safe use of dietary supplements. Several studies have found that pharmacists lack essential knowledge about vitamins, minerals, and other dietary supplements.…”
Section: Introductionmentioning
confidence: 99%